Implementation of Human Rights Certification as an Application for the Protection of Human Rights to Workers in the Fisheries Industry - Tito Pramudita (Jurnal Hukum Novelty, 2021)
Introduction to the Problem: State responsibility is one of the important keys in the life of the state, one of which is in labor affairs. In its implementation, there are several records of human rights violations in the Indonesian Sea, namely Trafficking in Persons, Forced Labor/Slavery, Child Labor, Overtime, and the absence of health insurance.Objective: This research aims to analyze the regulations in Indonesia concerning the protection of human rights for workers in the fishing industry in Indonesia and whether the Fisheries Human Rights Certification under the Regulation of the Minister of Maritime Affairs and Fisheries Number 35 of 2015 has effectively grant human rights protection to workers in the field of fisheries fishing industry in Indonesia.Methodology: The research method used is juridical-normative.Findings: This study indicates that Human Rights Certification in the Fisheries Sector is one solution so that fishing companies meet the Human Rights criteria set by the Government but still need improvement in the context and implementation. Conclusion Research on Fisheries Human Rights Certification has not been effective in protecting workers in the fishing industry from a technical and conceptual perspective. Effectiveness can be improved if there is an evaluation of problems in the form of overlapping authorities between agencies, the seriousness of the Fisheries Human Rights Team in carrying out its authority.Paper Type: Research Article